2000
DOI: 10.1161/01.atv.20.1.144
|View full text |Cite
|
Sign up to set email alerts
|

Oxidized VLDL Induces Less Triglyceride Accumulation in J774 Macrophages Than Native VLDL Due to an Impaired Extracellular Lipolysis

Abstract: Abstract-The present study examined the relative contributions of the different pathways by which oxidatively modified VLDL (oxVLDL) promotes the uptake and intracellular accumulation of lipids in J774 macrophages. VLDL was oxidized for a maximum of 4 hours, resulting in an increase in thiobarbituric acid-reactive substances and an increased electrophoretic mobility on agarose gel. The lipid composition of the relatively moderately oxidized VLDL samples did not differ significantly from that of nonoxidized VLD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
13
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 44 publications
0
13
0
Order By: Relevance
“…For example increased expression of UCP2 through a TNFα-dependent mechanism [34] has been described for hepatic tissue treated with LPS; increased hydrogen peroxide production by uncoupling proteins may result in oxidative modification of the resulting VLDL yielding efficient substrates for scavenger receptors. Moreover, oxidised VLDL had decreased binding to LPL [35] and induced less TAG accumulation in macrophages due to impaired LPL lipolysis [36]. Similar apo-E contents of both cVLDL and eVLDL [8] argues against enhanced uptake mediated through apo-E-specific routes.…”
Section: Discussionmentioning
confidence: 98%
“…For example increased expression of UCP2 through a TNFα-dependent mechanism [34] has been described for hepatic tissue treated with LPS; increased hydrogen peroxide production by uncoupling proteins may result in oxidative modification of the resulting VLDL yielding efficient substrates for scavenger receptors. Moreover, oxidised VLDL had decreased binding to LPL [35] and induced less TAG accumulation in macrophages due to impaired LPL lipolysis [36]. Similar apo-E contents of both cVLDL and eVLDL [8] argues against enhanced uptake mediated through apo-E-specific routes.…”
Section: Discussionmentioning
confidence: 98%
“…Third, FFA generated during the lipolysis of VLDL can also be brought into the cells via receptors or by passive diffusion (34). Macrophages are known to secrete active lipoprotein lipase (35), and lipoprotein lipase activity has been shown to be upregulated by exposure to VLDL (8,30). Our data showing the absence of TG and FFA accumulation in macrophages treated with the lipoprotein lipase inhibitor Orlistat are in agreement with other reports (30,33,36) and implicate VLDL remnant and/or FFA uptake as the primary mechanisms by which VLDL induces macrophage foam cell formation.…”
Section: Discussionmentioning
confidence: 99%
“…TGs in fasting plasma are carried in VLDLs, and these VLDLs have been found within human and experimental atherosclerotic lesions (3,4), providing a rationale to study their direct effects on macrophage functions such as foam cell formation and inflammation. It is well established that VLDL causes the accumulation of TGs and FFAs in macrophages (5)(6)(7)(8)(9). This can occur through three different mechanisms: 1) uptake of intact VLDL particles; 2) uptake of VLDL remnants resulting from lipoprotein lipase-mediated lipolysis; and 3) uptake of FFAs produced by VLDL lipolysis, which can be taken into cells through both passive diffusion and receptor-mediated mechanisms.…”
mentioning
confidence: 99%
“…2,3 Several studies indicated that oxLDL has a number of diverse effects on macrophage function including growth stimulation 4 proinflammatory effects such as expression of inflammatory cytokines, 5 increase in cytotoxicity and expression of metalloproteinases, 6 inhibition of expression of inducible nitric oxide synthase, 7 and effects on lipid metabolism and accumulation. 8,9 Using either a DNA array approach 10 or a subtractive approach, 11 numerous genes have been shown to be regulated on exposure of THP-1 cells to modified LDL. Adipophilin, or adipose differentiation-related protein (ADRP), a 50-kDa protein initially described in adipocytes, 12 which is considered a marker of lipid accumulation, is among those genes upregulated by modified LDL.…”
mentioning
confidence: 99%